Mass cytometric analysis unveils a disease-specific immune cell network in the bone marrow in acquired aplastic anemia - Pool, Emma S.; Kooy-Winkelaar, Yvonne; van Unen, Vincent; Falkenburg, J.H. Frederik; Koning, Frits; Heemskerk, Mirjam H. M.; Tjon, Jennifer M-L. (Frontiers in Immunology, 2023)
Idiopathic acquired aplastic anemia (AA) is considered an immune-mediated syndrome of bone marrow failure since approximately 70% of patients respond to immunosuppressive therapy (IST) consisting of a course of anti-thymocyte globulin (ATG) followed by long-term use of ciclosporin. However, the immune response that underlies the pathogenesis of AA remains poorly understood. In this study, we applied high-dimensional mass cytometry on bone marrow aspirates of AA patients pre-ATG, AA patients post-ATG and healthy donors to decipher which immune cells may be implicated in the pathogenesis of AA. We show that the bone marrow of AA patients features an immune cell composition distinct from healthy donors, with significant differences in the myeloid, B-cell, CD4 + and CD8 + T-cells lineages. Specifically, we discovered that AA pre-ATG is characterized by a disease-specific immune cell network with high frequencies of CD16 + myeloid cells, CCR6 ++ B-cells, Th17-like CCR6 + memory CD4 + T-cells, CD45RA + CCR7 + CD38 + CD8 + T-cells and KLRG1 + terminally differentiated effector memory (EMRA) CD8 + T-cells, compatible with a state of chronic inflammation.Successful treatment with IST strongly reduced the levels of CD16 + myeloid cells and showed a trend towards normalization of the frequencies of CCR6 ++ B-cells, CCR6 + memory CD4 + Tcells and KLRG1 + EMRA CD8 + T-cells. Altogether, our study provides a unique overview of the immune landscape in bone marrow in AA at a single-cell level and proposes CCR6 as a potential new therapeutic target in AA.